2014
DOI: 10.1001/jamapsychiatry.2014.1314
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk in Patients With First-Episode Schizophrenia Spectrum Disorders

Abstract: IMPORTANCEThe fact that individuals with schizophrenia have high cardiovascular morbidity and mortality is well established. However, risk status and moderators or mediators in the earliest stages of illness are less clear.OBJECTIVE To assess cardiometabolic risk in first-episode schizophrenia spectrum disorders (FES) and its relationship to illness duration, antipsychotic treatment duration and type, sex, and race/ethnicity. DESIGN, SETTING, AND PARTICIPANTS Baseline results of the Recovery After an Initial S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
240
9
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(275 citation statements)
references
References 80 publications
15
240
9
5
Order By: Relevance
“…In the EUFEST study, of individuals experiencing their first episode of schizophrenia, weight gain of 7% or greater of initial body weight was found in 65% of the follow-up population at 1 year (Kahn et al, 2008). In a study of individuals in the early stages of treatment for a first episode of psychosis, Correll et al (2014) found a pattern of increases in several metabolic risk indices after an average of 47 days of antipsychotic treatment.…”
Section: The Problemsmentioning
confidence: 99%
“…In the EUFEST study, of individuals experiencing their first episode of schizophrenia, weight gain of 7% or greater of initial body weight was found in 65% of the follow-up population at 1 year (Kahn et al, 2008). In a study of individuals in the early stages of treatment for a first episode of psychosis, Correll et al (2014) found a pattern of increases in several metabolic risk indices after an average of 47 days of antipsychotic treatment.…”
Section: The Problemsmentioning
confidence: 99%
“…90 In another recent study of young adults (15-40 years old) with first-episode schizophrenia spectrum disorders, 15.4 % (43/394) had hemoglobin A1c-defined prediabetes. 91 Women. In the Schizophrenia PORT field study (N = 719), Medicaid sample (N = 6066) and Medicare sample (N = 14,182), all found that women with schizophrenia had higher rates of diabetes than men (field study: 21.9 % vs 10.8 %, p < 0.001; Medicaid: 15 % vs. 4.3 %, p < 0.001; Medicare: 16.7 % vs. 8.8 %, p < 0.001).…”
Section: And Treatment Of Diabetes and Other Cardiovascular Disease Rismentioning
confidence: 99%
“…Smoking prevalence among persons with psychosis range from 44% to 77%, [5][6][7][8][9][10] with over 50% of 404 participants with first episode psychosis reporting current smoking in a recent treatment study. 11 People with severe mental illness (SMI) are also more likely to be heavy smokers (>1 ppd), 12 less likely to quit, 13 and die up to 25 years earlier than the general population, primarily due to smoking-related cardiac illness. 14 Almost one-third of current smokers in the United States have a mental illness 15 and smoking accounts for over half the illness-related deaths in persons with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%